Product quality improvement through Poka Yoke technique - Lee, Ing Yi (Faculty of Mechanical Engineering, 2007)

(untitled)
This paper focuses on a quality improvement project at JWS (company’s name abbreviated for confidentiality) using mistake proofing technique or Poka Yoke. The study is aimed at providing improvement ideas for existing problems at the manual assembly stations for product at D73A line. Investigations were conducted to identify causes of defects. Using results of unstructured interviews, and relevant data and from factory observations, the problem was analyzed using cause and effect diagram where the main causes were identified. To improve the existing problems, alternatives are generated using Poka Yoke and successive inspection techniques. Each alternative is evaluated in terms of its expected potential improvement and estimated cost of implementation. The evaluation indicates that Poka Yoke device proved to be the best alternative. This alternative was later presented to the company’s management for further evaluation and comments. The study culminates with proposed solutions to improve productivity at the factory and future study.